2016
DOI: 10.1136/annrheumdis-2016-eular.1810
|View full text |Cite
|
Sign up to set email alerts
|

FRI0299 Pulmonary Arterial Hypertension in Idiopathic Inflammatory Myopathies: Data from The French Pulmonary Hypertension Registry and Review of The Literature

Abstract: BackgroundOccurrence of pulmonary arterial hypertension (PAH) in idiopathic inflammatory myopathies (IIM) without extensive interstitial lung disease (ILD) has been rarely described.ObjectivesThis study aimed to report all cases with association of PAH and IIM in the French Pulmonary Hypertension (PH) Registry, to identify IIM features associated with PAH, and to describe treatment modalities of these patients.MethodsAll cases of IIM-PAH were retrieved from the French PH Registry, which gathers PAH patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The authors concluded that the best therapeutic strategies are yet to be defined in pSS-PAH. Finally, considering the nine cases reported by Sanges et al 24 in the French PAH registry, IIM-PAH does not appear to respond to glucocorticoids and/or immunosuppressants alone, whereas PAH-specific therapy appeared to be effective in stabilizing the disease.…”
Section: Immunosuppressantsmentioning
confidence: 89%
“…The authors concluded that the best therapeutic strategies are yet to be defined in pSS-PAH. Finally, considering the nine cases reported by Sanges et al 24 in the French PAH registry, IIM-PAH does not appear to respond to glucocorticoids and/or immunosuppressants alone, whereas PAH-specific therapy appeared to be effective in stabilizing the disease.…”
Section: Immunosuppressantsmentioning
confidence: 89%
“…102 A recently described series of nine patients identified DM subtype, skin involvement, and presence of anti-SSA autoantibodies as features more particularly associated with pulmonary hypertension in subjects with IIM. 102 Treatment of pulmonary hypertension using phosphodiesterase-5 inhibitors (sildenafil, tadalafil), endothelin receptor antagonists (bosentan, ambrisentan), and/or prostacyclin derivatives (intravenous epoprostenol, subcutaneous treprostinil, nebulized iloprost) should be reserved for the rare patients with PAH (i.e., without associated significant ILD), as group 3 pulmonary hypertension is believed to represent a complication of chronic hypoxia. 103 Distinguishing between group 1 PAH and group 3 pulmonary hypertension may be difficult, however, in subjects with ILD of mild to moderate severity.…”
Section: Other Lung or Thoracic Involvement Pulmonary Arterial Hypertmentioning
confidence: 98%
“…In the majority of cases, myositis-associated lung involvement takes a form of ILD. Unlike SSc, PAH is often secondary to ILD and isolated PAH is rarely found [ 151 ]. Although not a primary lung involvement of myositis, aspiration pneumonia and hypoventilatory respiratory failure are two serious complications related to pharyngeal and respiratory muscle involvement, respectively.…”
Section: Lung Involvement In Myositismentioning
confidence: 99%